The Meaning of Baptizein in Greek, Jewish, and Patristic Literature - Schnabel, Eckhard J. (Filología neotestamentaria, 2011)
The treatment of the Greek term Baptizein in the standard English lexicons is unsystematic. The use of the English term ‘to baptize’ for the Greek term Baptizein in English versions of the New Testament is predicated on the assumption that the Greek verb has a technical meaning which warrants the use of a transliteration. Since the first fact is deplorable and the second fact is unsatisfactory, an investigation into the meaning of the Greek term in Greek, Jewish, and patristic literary and documentary texts is called for in order to define the meaning of the term in classical and Hellenistic Greek with more precision than usually encountered in New Testament research, with a view to construct a more helpful lexicon entry for Baptizein.